Perceived stress and emotional intelligence as predictors of life satisfaction among undergraduates in Malaysia - Ooi, Yu Jie; Lim, Syi Wei; Cham, Han Tein (2022)
Life satisfaction has been found to be strongly correlated with both physical and psychological health-related issues. Hence, this cross-sectional and quantitative study was conducted to examine the predictive effect of perceived stress and sub-dimensions of emotional intelligence (self-emotion appraisal, others’ emotion appraisal, use of emotion, and regulation of emotion) on life satisfaction among undergraduates in Malaysia. A total of 110 were involved in the current study using both purposive and snowball sampling techniques. Online questionnaires were distributed across various social media platforms, which include Microsoft Teams, Facebook, Instagram, and WhatsApp. Participants were all undergraduates in the public and private universities in Malaysia with the age range between 19 to 24 (M = 21.72). About 43.6 % of respondents were males (n = 48), while about 56.4% were females (n = 62). Three instruments were applied in this study, which included Perceived Stress Scale (PSS-10), Wong and Law Emotional Intelligence Scale (WLEIS) and Satisfaction with Life Scale (SWLS). The findings revealed that perceived stress negatively predicted life satisfaction, while all sub-dimensions of emotional intelligence (self-emotion appraisal, others’ emotion appraisal, use of emotion, and regulation of emotion) positively predicted life satisfaction among Malaysian undergraduates. Thus, this study might provide a deeper insight on relevant topics and contribute significant references as well as directions to further researchers. Relevant authorities may be able to apply the knowledge in implementing new strategies, which may be useful for enhancing the life satisfaction of the undergraduates.